Cellular and Molecular Regulation of Inflammatory Pain, Nociception and Hyperalgesia - The Role of the Transcription Factor NF-κB as the Lynchpin Nocisensor: Hyperalgesic or Analgesic Effect? - Haddad, John J. (Current Immunology Reviews (Discontinued), 2007)
The milieu of inflammatory cells and inflammatory mediators is crucially involved in the genesis, persistence and severity of pain following trauma, infection or nerve injury. The mechanisms and pathways mediating pain and nociception (hyperalgesia) are transcriptionally regulated. The transcriptional mediator nuclear factor (NF)-κB plays a major role in regulating inflammatory responses, ostensibly via the control of gene expression/suppression. An association has recently emerged to establish a possible link between NF-κB and pain/nociception, purportedly through the regulation of the inflammatory loop and the secretion (biosynthesis) of pro-inflammatory mediators. Current concepts conspicuously indicate that the effective inhibition of this transcription factor and associated upstream kinase(s) and the pathways that regulate its nuclear translocation could be major targets in a new strategy for the alleviation of inflammation and inflammatory- related pain. In contrast, recent evidence has implicated NF-κB in analgesic effects; the mechanisms are yet to be elucidated. To better understand this relationship, therefore, between NF-κB and the evolution of pain and hyperalgesia/ nociception, it is imperative to unravel the molecular basis of this process. This survey integrates current themes pertaining to the pivotal role that NF-κB shares in regulating pain through the decoding of implicated molecular pathways and signaling mechanisms.
Keywords: pain